Risk factors for cardiovascular adverse events from immune checkpoint inhibitors - Luo, Lingli; Liu, Yuxin; Lu, Jingfen; Zhang, Yifei; Fan, Gang; Tang, Xiaojun; Guo, Weiming (Frontiers in Oncology, 2023)
Immune-related adverse events (irAEs), including skin injury, liver and kidney injury, colitis, as well as cardiovascular adverse events, are a series of complications arising during the treatment of immune checkpoint inhibitors (ICIs). Cardiovascular events are the most urgent and the most critical, as they can end life in a short period of time. With the widespread use of ICIs, the number of immune-related cardiovascular adverse events (irACEs) induced by ICIs has increased. More attention has been paid to irACEs, especially regarding cardiotoxicity, the pathogenic mechanism, diagnosis and treatment. This review aims to assess the risk factors for irACEs, to raise awareness and help with the risk assessment of irACEs at an early stage.